ANALISIS PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PERJUDIAN JENIS TOTO GELAP ONLINE - Texas Arnando (Indonesian Journal of Law and Islamic Law (IJLIL), 2021)
Gambling is a deliberate bet that is risking precious thing by realizing certain risks and expectations. such as the online lottery gambling case which had been decided by the Class IA of District Court of Tanjungkarang Number 978/Pid.B/2020/PN.Tjk. The result of the study reveals that criminal liability against black toto gambler online in Lampung namely by imprisonment for 1 (one) year while the judge's consideration in deciding the perpetrators was based on Decision Number 978/Pid.B/2020/PN.Tjk. including the demands of the public prosecutor, observe the indictment of the public prosecutor, listening to statements from witnesses, expert statements, statements of the defendant and evidence, legal facts revealed at trial, then consider the criminal elements of the defendant's actions seen from the Public Prosecutor's Indictment, If the criminal elements have been met, the Panel of Judges will give consideration to aggravating and mitigating factors for the accused.